Construction of the R17L mutant of MtC1LPMO for improved lignocellulosic biomass conversion by rational point mutation and investigation of the mechanism by molecular dynamics simulations. (December 2020) - Guo, Xiao; An, Yajing; Chai, Chengcheng; Sang, Jingcheng; Jiang, Luying; Lu, Fuping; Dai, Yujie; Liu, Fufeng
Highlights: Mt C1LPMO mutant was designed based on the HotSpot Wizard and dezyme web server. Mutant R17L exhibited a 1.8-times specific activity of wild type. Mutant R17L had an enhancing conversion efficiency of plant biomass. Molecular dynamics simulations clarified the mechanism for improved mutant R17L. This study will be beneficial to the rational design of highly active LPMOs. Abstract: To enhance the biomass conversion efficiency, the R17L mutant of the lytic polysaccharide monooxygenase (LPMO) Mt C1LPMO with improved catalytic efficiency was constructed via rational point mutation based on the HotSpot Wizard 3.0 and dezyme web servers. Compared with the wild-type (WT) Mt C1LPMO, R17L exhibited a 1.8-fold increase of specific activity and 1.92-fold increase of catalytic efficiency ( k cat /K m ). The degree of increase of the reducing sugar yield from microcrystalline cellulose and three plant biomass materials during synergistic hydrolysis using cellulase in combination with R17L was about 2 times higher than with the WT. Molecular dynamics simulations revealed that the R17L mutation reduced the stability of the region R18-I36, which then weakened the direct interactions between region N24-V31 and the substrate cellohexaose. Consequently, the deflection time of the cellohexaose conformation in R17L was prolonged compared to the WT, which enhanced its catalytic efficiency.